New treatments for systemic lupus erythematosus - Robert George Lahita (Indian Journal of Rheumatology)
New therapies for systemic lupus erythematosus are rare. This is because of the complexity of the disease and its varied presentations. There are many variables and a variety of measurement scales that must be satisfied before a new agent is approved for use in humans. Attempts are ongoing to develop biological treatments for the disease using three approaches: B cell modulation, T cell regulation and cytokine inhibition. This paper reviews the current state of these three critical areas.